BEHAVIOURAL SUPERVISION OF THE BANK OF RUSSIA IN PROTECTION OF FINANCIAL SERVICES CONSUMERS' RIGHTS - Irina V. Mikheeva (RUDN Journal of Law, 2020)
The article is devoted to a new type of supervision of financial market participants - behavioral supervision of the Bank of Russia. Behavioral approach to the protection of financial services consumers rights is treated in the zone of action of the administrative-legal regulation mechanism. The authors point to the public nature of the subject composition of its implementation (the Bank of Russia and the executive authorities); the possibility of using the judicial (consideration of citizens' appeals) and (as a result) jurisdictional (bringing the violators of the financial services consumers rights to administrative responsibility) procedural administrative and legal algorithms. The article outlines the types of the behavioral supervision regime of the Bank of Russia. Reactive behavioral supervision is a reaction of the Bank of Russia to complaints or received information about unfair behavior of the financial company towards the consumer. Preventive behavioral supervision is associated with the prevention of serious violations of citizens rights by supervised organizations. Particular attention is paid to consumer risks, the identification of which is one of the goals of behavioral supervision. Supervisory behavioral aspects are closely associated with the financial consumer protection as an important part of the control and supervising activity of the Bank of Russia. Also, the authors analyze the goals and content of behavioral approach to the financial management aimed at minimizing unfair practices. To gain the aim of the research the authors apply general scientific methods (synthesis and analysis, induction and deduction, generalizations) and special methods (formal-legal method). By using general scientific methods and formal-legal method authors investigate the organizational and legal basis for the implementation of behavioral supervision in Russia and determine its advantages and disadvantages. The study expresses assertion that there is the need to place behavioral supervision in the legislative framework, to formulate a definition of behavioral supervision, to clarify the scope and powers of the subjects of its implementation, to determine the content of administrative procedures for the implementation of various types of behavioral supervision within the framework of the interaction of the Bank of Russia and the executive bodies involved in its implementation.